Receptor phenomena and signaling pathways in the use of low doses insulin as a bio-restructuring agent in Aesthetic Medicine: promotes biological aging. Meta-analysis and systematic review of the literature - Svolacchia, Fabiano; Svolacchia, Lorenzo (Aesthetic Medicine, 2024)
The method of using low-dose insulin is indicated by some authors in aesthetic medicine as a technique for the bio-restructuring of tissues through the dermo-epidermal mesotherapy technique also in the areas of the face, neck and décolleté. The result of this off-label method will be that of an apparent aesthetic improvement, but with the formation of scar tissue and fibrosis in the injection tissue as well as in the surrounding tissues due to the inflammatory stimulus on the target cells and an excess production of Extracellular Matrix (ECM) deposited by fibroblasts with the formation of fibrotic tissue. In this meta-analysis and review of the literature, we delve into the mechanism it produces through which it triggers these effects and the aging process triggered through fibrosis in the tissues. Attention is also paid to any dosages and characteristics of the different types of insulins which can give different results up to the possible phenomena of pharmacological intolerance. This procedure will exclusively result in biological aging of the tissues.